2015
DOI: 10.1038/srep07691
|View full text |Cite
|
Sign up to set email alerts
|

Distinct p21 requirements for regulating normal and self-reactive T cells through IFN-γ production

Abstract: Self/non-self discrimination characterizes immunity and allows responses against pathogens but not self-antigens. Understanding the principles that govern this process is essential for designing autoimmunity treatments. p21 is thought to attenuate autoreactivity by limiting T cell expansion. Here, we provide direct evidence for a p21 role in controlling autoimmune T cell autoreactivity without affecting normal T cell responses. We studied C57BL/6, C57BL/6/lpr and MRL/lpr mice overexpressing p21 in T cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…Downregulation of interferon‐ γ may be related to higher p21 levels in the hyperoxia group at 3 months, as overexpressed p21 reduces T‐cell activation and interferon‐ γ secretion (Daszkiewicz et al. ). CD40–CD40 ligand interactions are critical for development of CD4 T‐cell‐dependent effector functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of interferon‐ γ may be related to higher p21 levels in the hyperoxia group at 3 months, as overexpressed p21 reduces T‐cell activation and interferon‐ γ secretion (Daszkiewicz et al. ). CD40–CD40 ligand interactions are critical for development of CD4 T‐cell‐dependent effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from severe suppression of immune genes following hyperoxia may be prolonged and dysfunctional in adult mice. Downregulation of interferon-c may be related to higher p21 levels in the hyperoxia group at 3 months, as overexpressed p21 reduces T-cell activation and interferon-c secretion (Daszkiewicz et al 2015). CD40-CD40 ligand interactions are critical for development of CD4 T-cell-dependent effector functions.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, it was reported that the therapeutic mechanism, although mediated by death ligands, did not involve apoptosis. This could be probably due to cell cycle inhibition mediated by the induction of p21 expression in activated T cells by exosome-bound FasL and/or TRAIL [115,116,117]. This mechanism is also influencing the pathogenesis of autoimmune lymphoproliferative syndromes due to mutations in Fas or FasL and should be kept in mind for their treatment [115].…”
Section: Exosomes In Autoimmune and Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…It is now established that, independently of this function, p21 is a central regulator of innate and adaptive immunity (39)(40)(41)(42)(43). p21 suppresses autoimmunity through T cell regulation (44), and we recently described a therapeutic effect for p21 through regulation of memory T cell responses and IFN-γ production in lupus-prone mice (45).…”
Section: Introductionmentioning
confidence: 99%